2004
DOI: 10.1038/nature02833
|View full text |Cite
|
Sign up to set email alerts
|

Tropism switching in Bordetella bacteriophage defines a family of diversity-generating retroelements

Abstract: Bordetella bacteriophages generate diversity in a gene that specifies host tropism. This microevolutionary adaptation is produced by a genetic element that combines the basic retroelement life cycle of transcription, reverse transcription and integration with site-directed, adenine-specific mutagenesis. Central to this process is a reverse transcriptase-mediated exchange between two repeats; one serving as a donor template (TR) and the other as a recipient of variable sequence information (VR). Here we describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
234
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(264 citation statements)
references
References 26 publications
11
234
1
2
Order By: Relevance
“…Analysis of these regions revealed that 12 resembled the diversity-generating retroelement of phage BPP-1 described above (6,8). This system is comprised of ∼100-bp repeat regions, the donor TR, the targeted VR, and an RT, which is required to mutagenize the VR at positions where the TR contains an adenine (6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of these regions revealed that 12 resembled the diversity-generating retroelement of phage BPP-1 described above (6,8). This system is comprised of ∼100-bp repeat regions, the donor TR, the targeted VR, and an RT, which is required to mutagenize the VR at positions where the TR contains an adenine (6).…”
Section: Resultsmentioning
confidence: 99%
“…A newly discovered mechanism of targeted hypermutation, particularly pertinent here, involves the Bordetella bacteriophage BPP-1, which has been shown to vary the sequence of the gene encoding its phage tail fiber to bind divergent cell-surface receptors (3)(4)(5)(6). The phage-encoded major tropism determinant (MTD) gene, which encodes the tip of the tail fiber, is subjected to targeted hypermutation by a reverse transcriptase (RT)-dependent mechanism (7,8).…”
mentioning
confidence: 99%
“…Interestingly, these examples all involve external proteins where structural changes are important to avoid immune recognition, to change surface attachment properties, or to permit interactions with different cell types. It is also noteworthy that bacterial DNA restructuring and protein engineering involve two features often thought to be limited to "higher" organisms: (i) repeat DNA sequences (Shapiro, 2002c) and reverse transcription (Doulatov et al, 2004).…”
Section: Bacteria As Natural Genetic Engineersmentioning
confidence: 99%
“…-flagellar phase variation in Salmonella (Zieg at el., 1977) -fimbrial phase variation in E. coli (Blomfield, 2001) -Borrelia VSG expression (Barbour et al, 2000) -R64 plasmid sex pilus structure changes (Gyohda et al, 2004) -Neisseria pilus and opacity protein changes (Saunders et al, 2000) -Bordetella reverse transcriptase (Doulatov et al, 2004) 2000). Thus, the DNA segments that move through the genome, the places they move, and the sequences they rearrange can have both flexibility and predictability.…”
Section: Bacteria As Natural Genetic Engineersmentioning
confidence: 99%
“…Collectively, these data underscore a role for complex RNA processing as another mechanism of immunological diversity. Other mechanisms can also introduce high levels of sequence diversity into receptor binding sites 135,136 , for example, when accompanied by an adjacent retroelement. …”
mentioning
confidence: 99%